Influence of work pressure and psychological distance on innovation behavior of employees in the sports industry - Jie Yang; Yuanjian Qin (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
This study examines the effects of work pressure and psychological distance on employees' innovative behavior in the sports industry. This study carried out a questionnaire survey to collect primary data. This paper systematically analyzed the influence mechanism and ways of job stress, goal orientation, and self-efficacy on employees' innovative behavior using a questionnaire survey. This relationship is analyzed by using primary data through a statistical tool. Results of the study highlighted that work pressure has a significant relationship with the innovation behavior of employees in the sports industry. Furthermore, it is found that psychological distance has a significant relationship with employees' innovative behavior in the sports industry. In enterprise management, managers should pay attention to the importance of innovation and build a cultural mechanism conducive to employee innovation; Improve the scientific management level of pressure, maintain appropriate work pressure and moderately exert challenging pressure; Guide employees to set work goals and pay attention to providing employees with a working atmosphere conducive to learning; Enhance employees' innovative self-efficacy to promote the long-term development of the enterprise.